Wage inequality and the changing organization of work - Dennis Görlich; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2010)
This paper sheds light on how changes in the organization of work lead to wage inequality. We present a theoretical model in which workers with a wider span of competence (higher level of multitasking) earn a wage premium. Since abilities and opportunities to expand the span of competence are distributed unequally among workers across and within education groups, our theory explains (1) rising wage inequality between groups, (2) rising wage inequality within groups, and (3) the polarization of work and the decoupling of the income distribution. Using a rich German data set covering a 20-year period from 1986 to 2006, we provide empirical support for our model.
Keywords: J31; J24; L23; 330; Wage inequality; tasks; multitasking; organizational change